Effect of urea phosphate foliar supplementation on yield, nutrient uptake and grain quality of rice (Oryza sativa L.) in acid Inceptisols - Monica, M; Dash, A K; Panda, N; Prusty, M (ORYZA-An International Journal of Rice, 2020)
Essential plant nutrient elements are generally applied to crops through soil to achieve more economic yields. Of the methods followed soil application is common and efficient for nutrients required in large quantities. However, under some situations crop responds better to foliar application along with blanket doses of fertilizers. Foliar application of urea phosphate (UP), an acidic nitrogen (N) and phosphate (P) nutrient fertilizers, along with blanket fertilizer doses can influence the yield as well as nutrient uptake and grain quality characteristicsof the crop rice. A field experiment was conducted to study the impact of urea phosphate on yield, nutrient uptake and grain quality of rice (Oryza sativa L.) in acid Inceptisols of Odisha, India. Different treatments were thus framed to test the hypothesis as T1-control (no nutrient); T2- 50% recommended dose of fertilizer (RDF); T3 -75% RDF; T4 -100% RDF; T5 -50% RDF + twice foliar spray (FS) of 1% UP; T6 -50% RDF + twice FS of 2% UP; T7 -75% RDF + twice FS of 1% UP; T8 -75% RDF + twice FS of 2% UP; T9 -100% RDF + twice FS of 1% UP and T10 -100% RDF + twice FS of 2% UP. Growth parameters like plant height (107.60 cm), panicle length (25.72 cm) and number of effective tillers per hill (13.58) were found to be highest in the plots where twice FS of 2% UPalong with 100% RDF was applied. The grain (4579.33 kg ha-1) and straw yield (5121.90 kg ha-1) of rice were also observed highest with T10 over T9, where 100% RDF + twice FS of 1% UP was applied. Uptake of nutrients like N (63.45 kg ha-1), P (18.36 kg ha-1 ) and K (96.85 kg ha-1) were found to be numerically higher in T10 where 100% RDF + twice FS of 2% UP was applied. The grain quality parameters of rice like protein content (R² = 0.624), alkali value (R² = 0.622) and amylose content (R² = 0.618) were significantly varied among the treatments.